Mainstreaming of Mobile Assistive Technology: Expertsâ?? Thoughts and Opinions - Kouroupetroglou, Christos; Tektonidis, Dimitris; Koumpis, Adamantios; Ignatiadis, Ioannis (International Journal of Interactive Mobile Technologies (iJIM), 2012)
This paper presents the outcomes from the interviews with experts and stakeholders that took part under the study on e-Accessibility2020[1] (â??Study on Implications from Future ICT Trends on Assistive Technology and Accessibility